1972
DOI: 10.4315/0022-2747-35.12.691
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria in Food and Health: A Review With Special Reference to Enteropathogenic Escherichia Coli as Well as Certain Enteric Diseases and Their Treatment With Antibiotics and Lactobacilli1

Abstract: Recent literature concerning enteropathogenesis and drug resistance transfer factors in Escherichia coli are summarized as well as related papers concerning the use of antibiotics in animal feed. E. coli infection in swine (colibacillosis) also is considered, especially citations indicating the similarity between the disease in man and animals. The role of intestinal bacteria in human health is reviewed, emphasizing the importance of (a) a maintained balance of organisms in the adult, (b) breast feeding in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(26 citation statements)
references
References 0 publications
0
24
0
2
Order By: Relevance
“…Regular consumption of these products can have a number of advantages as they contain physiological body-related bacteria (Sandine et al, 1972), have a generally larger content of L(+) lactic acid (Klupsch, 1983), correct various types of gastrointestinal disorders and maintain a favourable balance among the indigenous intestinal microflora (Schaedler et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Regular consumption of these products can have a number of advantages as they contain physiological body-related bacteria (Sandine et al, 1972), have a generally larger content of L(+) lactic acid (Klupsch, 1983), correct various types of gastrointestinal disorders and maintain a favourable balance among the indigenous intestinal microflora (Schaedler et al, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus acidophilus is a bile-resistant bacteria which can colonize in the intestines of humans and animals (Gilliland and Speck, 1977;Sandine, 1979;Sandine et al, 1972) acting as a probiotic (Brennan et al, 1983). Dietary supplementation with live L. acidophilus cells to maintain or improve intestinal health might be favorable, and has been advocated (Gilliland and Speck, 1977;Sandine, 1979;Speck, 1978) since antibiotic intake, digestive disorders, and abnormal and abusive food habits may diminish the multiplication and growth of L. acidophilus and reduce the number of this preventive microflora.…”
mentioning
confidence: 99%
“…In some studies it has been shown that when lactobacilli are implanted in the intestinal tract, there seems to be a suppressive effect on other members of the microflora (13,15). For example, it has been reported that antibioticassociated diarrhea and colitis have been controlled (5,11,15).…”
mentioning
confidence: 99%